A systematic review on the impact of gastrointestinal microbiota composition and function on cognition in healthy infants and children - McMath, Arden L.; Aguilar-Lopez, Miriam; Cannavale, Corinne N.; Khan, Naiman A.; Donovan, Sharon M. (Frontiers in Neuroscience, 2023)
Evidence from animal models or children with neurodevelopmental disorders has implicated the gut microbiome (GM) in neurocognitive development. However, even subclinical impairement of cognition can have negative consequences, as cognition serves as the foundation for skills necessary to succeed in school, vocation and socially. The present study aims to identify gut microbiome characteristics or changes in gut microbiome characteristics that consistently associate with cognitive outcomes in healthy, neurotypical infants and children. Of the 1,520 articles identified in the search, 23 were included in qualitative synthesis after applying exclusion criteria. Most studies were cross-sectional and focused on behavior or motor and language skills. Bifidobacterium, Bacteroides, Clostridia, Prevotella, and Roseburia were related to these aspects of cognition across several studies. While these results support the role of GM in cognitive development, higher quality studies focused on more complex cognition are needed to understand the extent to which the GM contributes to cognitive development.